2001
DOI: 10.1088/0305-4470/34/41/303
|View full text |Cite
|
Sign up to set email alerts
|

Ageing and memory phenomena in magnetic and transport properties of vortex matter

Abstract: There is mounting experimental evidence that strong off-equilibrium phenomena, such as "memory" or "aging" effects, play a crucial role in the physics of vortices in type II superconductors. In the framework of a recently introduced schematic vortex model, we describe the out of equilibrium properties of vortex matter. We develop a unified description of "memory" phenomena in magnetic and transport properties, such as magnetisation loops and their "anomalous" 2nd peak, logarithmic creep, "anomalous" finite cre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 107 publications
0
23
0
Order By: Relevance
“…6 for r T RM and plotting the outcome versus log 10 t obs reproduces the well known shape of S(t): a broad maximum is present at t obs = t w , and a flat asymptotic value, equal to a, is reached for t obs ≫ t w . The asymptotically logarithmic TRM decay and, equivalently, the constant asymptotic value of S are widely observed in complex systems, To name a few cases, they are seen in switchable mirrors after UV illumination [27], in the field-cooled magnetization of spin glasses [28], and in the magnetic creep of the ROM model [29] of magnetic flux creep in type II superconductors [21]. In the asymptotic regime, the rate is r T RM ∝ 1/t, and the time at t w at which the perturbation is switched off is thus forgotten.…”
Section: Theorymentioning
confidence: 99%
“…6 for r T RM and plotting the outcome versus log 10 t obs reproduces the well known shape of S(t): a broad maximum is present at t obs = t w , and a flat asymptotic value, equal to a, is reached for t obs ≫ t w . The asymptotically logarithmic TRM decay and, equivalently, the constant asymptotic value of S are widely observed in complex systems, To name a few cases, they are seen in switchable mirrors after UV illumination [27], in the field-cooled magnetization of spin glasses [28], and in the magnetic creep of the ROM model [29] of magnetic flux creep in type II superconductors [21]. In the asymptotic regime, the rate is r T RM ∝ 1/t, and the time at t w at which the perturbation is switched off is thus forgotten.…”
Section: Theorymentioning
confidence: 99%
“…In addition to transient effects, pronounced memory effects and hysteretic V(I) curves have been observed near the peak effect in low temperature materials [2,[4][5][6][7][16][17][18][19][20]. Memory effects are also seen in simulations [22]. Xiao et al [7] have shown that transient behavior can lead to a strong dependence of the critical current on the current ramp rate.…”
mentioning
confidence: 98%
“…their properties slowly change with the waiting time, t w , elapsed from the quench. Ever since the initial observations in polymers [1], evidence has accumulated that spin-glasses [2], type II superconductors [3], glasses [4], and soft condensed matter [5], among others, age in similar ways, e.g. : For observation times t ≪ t w physical averages are nearly constant, and autocorrelations and their conjugate linear response functions are connected by an equilibrium-like fluctuation-dissipation theorem (FDT).…”
mentioning
confidence: 99%